Negative Mass - Tannous, Edward (Journal of natural sciences, life and applied sciences, 2021)
This article presents a physical model, which describes the ideas of special relativity, in a more rational, logical, simple and understandable manner, while using basic mathematical tools. The model is based on Albert Einstein’s formula, which describes the “rest” energy of a body with mass m, given by the formula E = mc2. Based on this formula, and in accordance with the theory of special relativity, we present here a model of a body, moving at a constant velocity in space with speed equal to the speed of light in space-time, determined by an “energy angle” and negative mass. This model also presents a method for creating negative mass, a calculating method for the relative velocity, and a method for calculating energy and momentum, in a completely elastic collision and plastic collision, differing from contemporary nowadays methods, using classical and modern physics. In addition, the new model solves better the problems and paradoxes known in special relativity physics, such as the Twin Paradox and others. All this in Part 1, in Part 2 we will discuss the application of the model to the body under the influence of gravitational forces and in Part 3 we will see how phenomena in quantum physics can be explained according to the same model.